Intelligent Door Knocking Security System Using IOT - et. al., Dr. T. J.Nagalakshmi , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In current day security is very important. Nowadays, in all places many robberies are going on. In this security issue, lock is the major parameter. The trustworthy on the lock should me made improve. The lock may be for main door lock, baggage lock, shutter lock, grill door lock, interconnecting door lock etc. This project is based on arduino board and IOT. And also this can be used for main door and for locker door. This lock works based on the knocking pattern. The owners knocking pattern is stored in the register. When the knocking pattern is detected by the sensor, it passes it to the arduino board microcontroller. Based on the trustworthiness of the pattern the lock works. This framework is easy for installation. It can be implemented for commercial use also.